Investigation of fuel properties and structural-functional group analysis in blending low and high boiling point fuels: the case of ethanol with fuel - Annisa Bhikuning; Budi Setiawan; Jamal F. Jati; Jefa D. I. Wijaya; Muhammad Hafnan (Jurnal Polimesin, 2023)
For numerous decades, diesel fuel has served as the primary source of energy for diesel engines. For optimal performance, these engines are designed to withstand a high flammability threshold. Diesel fuel is therefore the preferable option for refueling military combat vehicles, particularly battle tanks. Concerns have been expressed regarding the use of diesel fuel due to its potential contribution to environmental pollution; emissions from combustion include NO2, NO, CO, SO2, and particulate matter. To reduce these emissions, diesel fuel must be blended with another substance. To reduce emissions, ethanol incorporation is a potential solution. A previous study demonstrated that combining fuels with high and low boiling points can enhance performance. Mixing ethanol, which has a low boiling point, with biodiesel/diesel fuel and fuel with a high boiling point can produce a superior fuel. Analyzing the characteristics of the fuels produced by merging ethanol with diesel fuel and biodiesel is crucial. This analysis aids in the comprehension of the fuel's physical properties prior to its use in a diesel engine. In this investigation, Indonesian diesel fuel and biodiesel standards are blended with ethanol at 10%, 25%, and 35% (volume) blending ratios. In addition to utilizing FTIR (Fourier Transform Infrared Spectroscopy) for analysis, the objective of this study is to determine the combustion properties of a blend of biodiesel, diesel fuel, and ethanol. Using the American Society of Testing Materials (ASTM) D method, fuel properties such as density, viscosity, cetane index, and distillations are analyzed. The results indicate that increasing the proportion of ethanol in diesel fuel and biodiesel reduces viscosity and density. By integrating ethanol, which has a lower density and viscosity than diesel fuel and biodiesel alone, the fuel properties can be improved. A perfect blend of ethanol, diesel fuel, and biodiesel can increase the quality of fuel, thereby enhancing diesel engine combustion.